A case report of Kounis syndrome presenting with a rash, very late stent thrombosis and coronary evaginations. Issue 1 (11th February 2020) - Fujisaki, Tomohiro; Higa, Tomitaka; Uechi, Yoichi; Maehira, Naoya
Abstract: Background: Very late stent thrombosis (ST) is a concern in the era of drug-eluting stents (DESs), and ST is associated with peri-DES coronary artery aneurysmal lesions or coronary evaginations. An increasing number of cases of concurrent systemic allergic reaction and ST have been reported as Kounis syndrome (KS) in the literature. The number of patients with very late ST caused by KS is small, and further investigation of the potential pathophysiology is required. Case summary: We report a case of KS that manifested as systemic urticaria followed by very late ST 14 years after placement of two sirolimus-eluting stents (SESs). Three months after the event of ST, coronary evaginations at the stented segments were detected on intravascular optical coherence tomography. Discussion: Coronary evaginations are associated with local hypersensitivity, stent malapposition, uncovered strut, and flow disturbance that may predispose to ST. Systemic allergic reactions are known to promote platelet adhesion and aggregation. This case of KS suggests a pathophysiology in which the synergic effects between the coronary evaginations and a systemic allergic reaction may contribute to very late ST. For patients with Type 3 KS, performing follow-up intracoronary imaging tests may be important to confirm potential coronary evaginations, especially in patients with SESs.